Everyday urbanisms and the importance of place: Exploring the elements of the emancipatory smart city. (February 2021) - Odendaal, Nancy
Two of the most striking features of smart city discourses are the centrality of technology as a driver of transformational change and the strange 'placelessness' of its visual narrative. Whether envisaged in Kenya or Singapore, the commercial smart city is represented as a 'city in a box', seemingly capable of solving complex social issues through algorithms and technical innovation. Recently a robust literature has emerged that is critical of the techno-determinism inherent in smart city discussions. This paper expands on this critique by arguing that by solely focusing on the material dimensions of technologically informed urban change, devoid of context, we miss an opportunity to uncover an important moment in contemporary urbanity. By foregrounding the human dimensions of technology appropriation and the interface with livelihoods in their particular spatial contexts, this paper consciously decentres the dominant smart city discourse by arguing for the foregrounding of local dynamics. This paper rejects the universalisms embedded in smart city promises and argues that by provincialising the idea of smart urbanism, opportunities are presented for understanding the true markers of contemporary urbanism. Critical debates on the smart city, and by extension the need to consider smart urbanism contextually and as an infrastructure, relationally, together with the conceptual insights provided by postcolonial science and technology studies, contribute to a proposed frame for researching the ongoing dynamic between contemporary urban life and technological innovation. Empirical vignettes from urban Africa are used to illustrate the multiple dimensions of the interface between livelihoods and technology appropriation.